Impact of exoD gene knockout on the polyhydroxybutyrate overaccumulating mutant Mt_a24. Issue 1 (1st January 2021) - Mittermair, Sandra; Richter, Juliane; Doppler, Philipp; Trenzinger, Kevin; Nicoletti, Cecilia; Forsich, Christian; Spadiut, Oliver; Herwig, Christoph; Lackner, Maximilian
ABSTRACT: New possibilities for sustainable and climate-friendly plastic production are urgently needed. One degradable alternative could be polyhydroxybutyrate naturally produced out of CO2 via photosynthesis within cyanobacteria. Therefore, the polyhydroxybutyrate production of the so far little investigated polyhydroxybutyrate overproducing Synecho-cystis sp. PCC6714 mutant Mt_a24 should be further increased. The impact of reducing the exopolysaccharide production on the polyhydroxybutyrate yield was examined by knocking the exoD gene out. The generated transformants KOexoD #4 and KOexoD #65 were compared to the control strain under standard and nutrient limiting cultivation conditions regarding their growth, glycogen, polyhydroxybutyrate and exopolysaccharide production. Whereas the growth of all three strains was comparable under standard conditions, only minor differences could be detected under limited conditions. An increase of polyhydroxybutyrate could be observed in both transformants ( KOexoD #4: 1.17-fold, KOexoD #65: 1.26-fold) under limited conditions. The exopolysaccharide production was increased in both transformants under standard cultivation conditions, showing a strong increase of soluble exopolysaccharides. In contrast, during limitation, the soluble exopolysaccharides decreased in all cultures whereas the tightly bound exopolysaccharides fraction strongly increased. Hence, the influence of limiting medium, and connection to the energy storage pathways could be shown as well as the great potential of Mt_a24 as a sustainable production system for polyhydroxybutyrate.